Cytotoxic tigliane-type diterpenoids from Croton tiglium. Issue 52 (30th December 2015) - Zhang, Dong-Dong; Zhou, Bin; Yu, Jin-Hai; Xu, Cheng-Hui; Ding, Jian; Zhang, Hua; Yue, Jian-Min
Abstract: Chemical study on the twigs and leaves of Croton tiglium has led to the isolation of 11 new tigliane-type diterpenoids, crotignoids A–K (1 –11 ), along with eight known analogues (12 –19 ). The structures of these compounds were elucidated on the basis of detailed spectroscopic analysis. In vitro cytotoxic assays revealed moderate inhibition of compounds1 –10 toward human HL-60 and A549 tumor cells, with1 exhibiting the strongest activity against HL-60 cell line with an IC50 value of 1.61 μM. Graphical abstract: